Cellulase immobilized on a composite carrier. - Ahmadun, Fakhru'l-Razi; Hassan, Mohd Ali; Danafar, Firoozeh; Mohd Salleh, Mohamad Amran; Awang Biak, Dayang Radiah (2010)

(untitled)
The present invention discloses a method for the production of an immobilized cellulase, which comprises preparing a carrier suspension comprising a mixture of chitosan and carbon nanotube solutions, adding the carrier suspension to a base solution to form beads, drying the beads to form a carrier in the form of flakes and adding the carrier flakes to a cellulase enzyme solution, thereby forming an immobilized.